Monarchy, Symbolic Legitimacy, and Institutional Performance in Shaping Democratic Satisfaction in the United Kingdom and the Netherlands - Zakky Zidan; Idris Hemay (Jayapangus Press, 2026)
This study examines how symbolic legitimacy and institutional performance interact to shape democratic satisfaction amid declining public trust in political institutions. Focusing on the United Kingdom and the Netherlands as contrasting majoritarian and consensus constitutional monarchies, it investigates whether trust in the monarchy increases democratic satisfaction, whether institutional performance strengthens this effect, and whether the magnitude differs across system types. Using a quantitative comparative design based on World Values Survey Wave 7 data, the study applies weighted logistic regression and interaction models to estimate direct and conditional effects. The findings show that trust in the monarchy is positively associated with democratic satisfaction and that this effect becomes stronger when citizens perceive representative institutions as performing effectively. Cross-system comparison further indicates that symbolic legitimacy plays a stronger role in the United Kingdom, where it functions more compensatorily within an adversarial political setting, while in the Netherlands it operates more complementarily within a consensus-oriented institutional environment. The study concludes that democratic legitimacy in constitutional monarchies is dual and context-dependent, emerging from the interaction between symbolic attachment and institutional performance. It contributes theoretically by clarifying the relationship between symbolic and performance-based legitimacy and methodologically by demonstrating the value of cross-national comparative modelling.